Chlorhexidine Cleansing of the Umbilical Cord and Cord Separation Time: A Hospital Based Study in Bangladesh - Khairuzzaman, Md.; Mannan, MA; Matin, Abdul; Sarker, Mst. Monjuman Ara; Sarker, Nihar Ranjan; Mowla, Md. Golam; Shahidullah, Mohammod (Journal of Science Foundation, 2016)
Background: Cord separation time has evolved as an important justification for recommending against the topical use of chlorhexidine on the cord. Objective: This present study was undertaken to determine the impact of cord cleansing with chlorhexidine on cord separation time and maternal acceptance of chlorhexidine in umbilical cord care. Methods: Between April 2013 to July 2014, 340 newborns were randomly assigned within a tertiary level hospital in Bangladesh to receive 1 of 2 cord care regimens: clean and dry cord care (control) and single cord cleansing with 4% chlorhexidine. Results: The mean cord separation time in newborns of chlorhexidine group was significantly longer than dry cord care group (p < 0.001). Mother of newborns in chlorhexidine group more frequently reported longer than usual cord separation time. Overall satisfaction of mother with cord separation time was high (95.9%). Conclusion: Topical chlorhexidine significantly increased cord separation time. Journal of Science Foundation, 2015;13(2):27-30 DOI: http://dx.doi.org/10.3329/jsf.v13i2.27929